Noise as an external effect of traffic and transportation - Starčević, Slobodan M.; Bojović, Nebojša J. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The paper deals with the basic concepts and characteristics of external effects of traffic and transport, with an emphasis on the impact of traffic noise as one of the main external effects of transport nowadays. The main negative impacts of traffic noise on human life and social activities are given as well as the causes of elevated levels of noise from road, rail and tram traffic. In addition, the paper provides a review of the common measures that can be applied to reduce the impact of noise generated as a result of traffic and transport activities. In the end, we made a short review of the current situation regarding the impact of traffic noise in the Republic of Serbia and the Serbian Armed Forces.
Keywords: Transportation; Noise